Best practices of financial sustainability: The case of accelerated development of Korean non-profit organizations (2015)
The success of Beyoungri Danche depends on the financial strategies that its leaders use to make them sustainable over time. The compilation of good practices of Korean Beyoungri Danche in literature and an exploratory investigation of web content from three successful organizations, allows to learn tactics of another culture that has demonstrated a high organizational level and strengthen the dialogue around a topic of common interest.